Excel Track - Preston, E. (The Professional Skater PS Magazine, 2018)
As part of the new Excel track, die U.S. Figure Staling Program Development Committee introduces the Exel Challenge Series in the 2018-19 season. Details about this new program will follow! Download the Excel Elements Chart, which will take effect September 1. 2018. The chart is available on the U.S. Figure Skating website (under Programs: Excel).